02.08 The paracaspase malt1 plays a central role in the pathogenesis of rheumatoid arthritis. (1st March 2017) - Gilis, Elisabeth; Staal, Jens; Beyaert, Rudi; Elewaut, Dirk
Abstract : Background: Rheumatoid arthritis (RA) is characterised by the activation of auto-reactive T-cells and the development of auto-antibodies. Importantly, T-cells may additionally respond to non-TCR mediated signals, which are essential in driving their effector functions. Pathways leading to the modulation of both innate and adaptive signals are therefore of marked interest to study in arthritis. The paracaspase MALT1 is a key player in the activation of lymphoid, myeloid and mast cells, indicating MALT1's crucial role in innate and adaptive signalling. Therefore, MALT1 is regarded a promising target for the treatment of autoimmune diseases and defining its role in the pathogenesis of RA is a critical first step. Methods: To unravel MALT1's role in RA, we initially assessed MALT1-activation in mice challenged with collagen-induced arthritis (CIA), the prototype model for RA. We then sought to address MALT1's role in the pathogenesis of RA by subjecting MALT1-deficient mice to distinct models of arthritis (CIA and CAIA). To determine the importance of MALT1 in T-cells, CIA was additionally induced in CD4-specific MALT1-deficient mice. Finally, the effect of MALT1-deletion on bone homeostasis was assessed by measuring bone density by µCT-analysis of the tibiae and by a three-point bending test of the femurs. Results: We provide evidence that MALT1 is activated in RA and plays a crucial role in its pathogenesis since MALT1-deficent mice were completely protected against CIA. This protection was additionally observed in CD4-specific MALT1-deficient mice, indicating that the selective ablation of MALT1 in CD4-positive cells is sufficient for the observed resistance. CAIA on the other hand, which is a T-cell independent model of RA, did not depend on MALT1 since both MALT1 +/+ and MALT1 -/- mice showed comparable arthritis symptoms. Paradoxically to the protective effect of MALT1-deletion on inflammation, we show that MALT1-deficiency negatively influences bone density at steady state. More specifically, both the tibiae and femurs of MALT1 -/- mice had a significantly reduced bone density and strength compared to MALT1 +/+ mice. Conclusion: Altogether, our data provide evidence for a dual role of MALT1 in arthritis, showing a protective effect of its deletion on the inflammatory aspect and a negative effect on bone homeostasis.